HYDROGEOCHEMICAL PRECURSORS OF STRONG EARTHQUAKES: A REALISTIC POSSIBILITY IN KAMCHATKA - Kingsley S.P.; Biagi P.F.; Piccolo R.; Capozzi V.; Ermini A.; Khatkevich Y.M.; Gordeev E.I. (My University, 2001)
The Kamchatka peninsula, located in the far East of Russia, is characterised by frequent and strong seismic activity (magnitudes up to 8.6). For many years, samples for hydrogeochemical analyses have been collected with a mean sampling frequency of three days in the form of the pH values and of the most common ions and gases in the groundwater of some deep wells and springs in the south area of the Kamchatka peninsula, where the capital city Petropavlovsk is located. In the last ten years, five earthquakes with M>6.5 have occurred at distances of less than 250 km from the measurement sites. In order to reveal any possible precursors of these earthquakes, the hydrogeochemical data collected from three wells have been analysed. We have identified 12 anomalies with 8 of them being possible successes and 4 failures as earthquake precursors and we have obtained a probability of 67% that any given hydrogeochemical anomaly is an earthquake precursor. One of the results obtained indicates that the possibility of observing precursors in the hydrogeochemical parameters of a well seems to be related to the location of an earthquake with respect to the well. Recently, this behaviour was confirmed when we observed a clear co-post seismic effect in only one well after an earthquake on December 5, 1997, which was about 400 km distant and very strong (M=7.7).
Keywords: Kamchatka; Earthquakes; Precursors